On the Basic Concepts of UWB Radar Scan - Astanin, L.Yu.; Kostylev, A.A.; Fliorova, A.A. (Радиофизика и радиоастрономия, 2002)
In this paper, the terms in wide use, the Ultra Wideband (UWB) signal and the Ultra Shot Impulse (USI), are discussed. Their usage conditions are considered and the difference in meanings is determined. As main tool for describing the power requirements to UWB Radar, the generalized Radar Range Equation (RRE) valid to arbitrary width of the spectrum is employed. The assumptions as to the UWB Radar characteristics allowing to represent the RRE in similarity to the traditional form are considered. The use of the Impulse Active Antenna Array can be a way to the UWB power problem solution. The problems regarding the high peak power UWB signals are posed. It is possible, as demonstrated, to produce the complex UWB pulse signal with large timebandwidth product. Предметом обсуждения являются два общеизвестных термина: сверхширокополосные (СШП) сигналы и ультракороткие импульсы (УКИ). Рассматривается условия их употребления и различие в значении. Обобщенное основное уравнение локации (ОУЛ), верное для сигналов с произвольной шириной спектра, применяется как основное средство описания энергетических требований к СШП радарам. Рассмотрены допущения относительно характеристик СШП радаров, позволяющие представить ОУЛ в форме, похожей на традиционную. Использование импульсных активных антенных решеток может быть способом решения проблем энергетики СШП сигналов. Поставлены задачи, касающиеся высокой пиковой мощности СШП сигналов. Показано, что можно получать сложные СШП импульсные сигналы с большой базой сигнала. Предметом обговорення є два загальновідомі терміни: надширокосмугові (НШС) сигнали та ультракороткі імпульси (УКІ). Розглянуто умови їх вживання та різниця у значенні. Узагальнене основне рівняння локації (ОРЛ), що є вірним для сигналів з довільною шириною спектру, застосовується як основний засіб описання енергетичних вимог до НШС радарів. Розглянуто припущення щодо характеристик НШС радарів, що дозволяють представити ОРЛ у формі схожій на традиційну. Застосування імпульсних активних антенних решіток може бути засобом вирішення проблем енергії НШС сигналів. Поставлено задачі щодо високої пікової потужності НШС сигналів. Показано, що виявилось можливим отримувати складні НШС імпульсні сигнали з великою базою сигналу.